AZ-97 (Oryza sativa ssp. Indica) exhibits superior biomass production by maintaining the tiller numbers, leaf width, and leaf elongation rate under phosphorus deficiency - Yasuhiro Tsujimoto; Mitsukazu Sakata; Viviane Raharinivo; Juan Pariasca Tanaka; Toshiyuki Takai (Plant Production Science, 2021)
Shoot morphology in rice plants changes in response to P deficiency. However, how genotypic variations in these morphological changes affect the canopy development and biomass production have hardly been explored. The study aimed to identify specific shoot morphological traits that confer biomass production under P deficiency. Four rice genotypes, including AZ-97 (WAS 63–22-5-9-10-1), which exhibits high performance under highly P-deficient fields in Madagascar, were grown for 56 days in flooded pots over several P application rates to simulate P-sufficient and moderately, severely, and extremely P-deficient conditions. AZ-97 had superior shoot P contents and biomass than Takanari, a high-yielding cultivar, and X265, a common high-yielding cultivar in Madagascar at severely to moderately P-deficient conditions. Shoot biomass was highly correlated with projected leaf area (PLA) from the early growth stage, and tiller number, leaf width, and leaf elongation rate explained the variations in PLA. These morphological traits reduced significantly with decreased P application rates, while reduction in AZ-97 was small relative to the other genotypes, even for equivalent shoot P contents. As the result, AZ-97 had greater PLA per unit of shoot P content at equivalent shoot P contents. The result indicates that lower sensitivity and degrees of change in shoot morphology when exposed to P deficiency stress could be a key trait facilitating the maintenance of captured radiation and subsequently influencing genotypic differences in external P uptakes and biomass production. AZ-97 is a potential donor with such traits that can offer an additional avenue for genetic improvement toward P-efficient rice production.Abbreviations DAT: days after transplanting; LN: leaf number in the main stem; PLA: projected green leaf area; PUE: phosphorus use efficiency; SSA: Sub-Saharan Africa.